Macronutrient contents in rose crops under salinity levels and nitrogen:potassium ratios - da Silva, Everaldo Moreira; Souza Lima, Carlos José Gonçalves; de Miranda, Jarbas Honorio; Ribeiro, Aureliano Albuquerque; Duarte, Sérgio Nascimento (Comunicata Scientiae, 2018)
Rose crops under fertigation in a protected environment is an alternative for production increase. However, the high dosages of fertilizers can lead to the salinization of soils in this environment. The aim of this study was to evaluate the effect of salinity caused by the excess of fertilizer application through fertigation associated with different nitrogen: potassium (N: K) ratios on macronutrient contents in rose crops. The study was performed in a randomized block design, arranged in a factorial scheme (5 x 3 + 1), with four repetitions, totaling 64 plots. The treatments were formed by combination of five initial levels of electrical conductivity (EC: 1.2; 2.3; 3.3; 4.3 e 5.5 dS m-1), three nitrogen: potassium (N: K) ratios (2:1; 1:2 and 1:3) and a control with N: K ratio (1: 1). Contents of N, K, Ca, Mg and S were evaluated in the stem, leaves and flowers. The levels of N, K, P, Ca and Mg in plant tissues are affected by the treatments at 245 days after transplanting. Leaves presented the highest levels of macronutrients, mainly nitrogen. TDR probe is a satisfactory tool in the management of fertigation.